Fabrication and characterization of electrospun GelMA/PCL/CS nanofiber composites for wound dressing applications - TINAZ, GÜLGÜN; GÜNDÜZ, OĞUZHAN (My University, 2022)
In the present study, the effect of different ratios of GelMA concentration has been exhibited for wound dressing implementation by the electrospinning method using a new polymer combination of Gelatin methacrylate (GelMA)/Polycaprolactone (PCL)/Chitosan (CS). The nanofiber composites were fabricated due to their biocompatible, biodegradable, improved mechanical strength, low degradation rate, and hydrophilic nature to develop cell-mimicking, cell adhesion, proliferation, and differentiation. Different concentrations of GelMA were added to the PCL/CS solution as 5, 10, and 20 wt%, respectively, in the formic acid/acetic acid (7:3) solution. A photoinitiator was added to the solution for photo-crosslinking of GelMA. The influence of different solution concentrations (5, 10, and 20 wt%) on the structure\"s nanofiber production and fiber morphology was examined. SEM micrographs revealed that varied GelMA concentrations resulted in suitable and stable nanofiber composites. The average diameter of nanofiber composites grows as the GelMA concentration rises. FTIR, DSC, tensile test, degradation, and swelling test were evaluated. The results demonstrated that high mechanical strength, hydrophilic properties, and a slow degradation rate were observed with the presence and increment of GelMA concentration within the nanofiber composites. The antibacterial potential of GelMA/PCL/CS nanofiber composites was evaluated against P. aeruginosa and S. aureus using a disc diffusion assay. In vitro cell culture research was conducted by seeding NIH 3T3 fibroblast cells on nanofiber composites, proving these cells\" high cell proliferation rate, viability, and adhesion. 10 wt% GelMA-based nanofiber composites were found to have great potential for wound dressing applications.
Keywords: Yaşam Bilimleri; Biyoteknoloji; Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Mühendislik ve Teknoloji; Life Sciences; Biotechnology; Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; Engineering and Technology; BİYOTEKNOLOJİ VE UYGULAMALI MİKROBİYOLOJİ; Mikrobiyoloji; Yaşam Bilimleri (LIFE); MALZEME BİLİMİ, BİYOMATERYAL; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); POLİMER BİLİMİ; Temel Bilimler (SCI); BIOTECHNOLOGY & APPLIED MICROBIOLOGY; MICROBIOLOGY; Life Sciences (LIFE); MATERIALS SCIENCE, BIOMATERIALS; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); POLYMER SCIENCE; CHEMISTRY; Natural Sciences (SCI); Polimerler ve Plastikler; Biyomalzemeler; Malzeme Bilimi (çeşitli); Genel Malzeme Bilimi; Uygulamalı Mikrobiyoloji ve Biyoteknoloji; Kimya (çeşitli); Genel Kimya; Moleküler Tıp; Fizik Bilimleri; Polymers and Plastics; Biomaterials; Materials Science (miscellaneous); General Materials Science; Applied Microbiology and Biotechnology; Chemistry (miscellaneous); General Chemistry; Molecular Medicine; Physical Sciences; Electrospinning; biomaterials; wound dressing; GelMA; CROSS-LINKING; MECHANICAL-PROPERTIES; HYDROGELS; SCAFFOLDS; RELEASE